(3CNdU GdNGdUIs - (3GdHONTGfj, GdHONTGfj, Ydj Hf eMehO Hf eMeO GdQGHV GdHONTGfj, J HYO (B909(3g` (B1503(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdCMO GdbOje GdSdGe GdUeO GdbOjQ GdYdGe NGdb (B... (3aj GdYbd bGd Cgd GdYde GdYbdj LhgQ eVjA Ndbg Gddg JYGdis
(3BNQgG (B:s
(3BNQgG(B: (3Qhj Cf OGhO (B.. (3SLO HYO eG hbY GdRdRdI hHci HcGA TOjOG hbGd(B: (3fYeJfj ade JLOfj TGcQG, hGHJdjJfj ade JLOfj UGHQG, bGd YPHfj aCfG Cgd dPdc hEf JZaQ dj aCfJ Cgd dPdc CfJ HGdaVd hGdcQe hGddWa ehUha hHGdMde hGdYah hGZaQGf eYQha hCfG GdYHO GdVYjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 20s
(3GdCYdGe, L (B5: 20s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs